ANALISIS KINERJA JARINGAN WLAN MENGGUNAKAN METODE ACTION RESEARCH PADA DUKCAPIL KOTA PALANGKA RAYA: Analysis Of WLAN Network Performance Using Action Research Method at DUKCAPIL Kota Palangka Raya - Pratama, Agus; Windiarti, Ika Safitri; Haryadi, Haryadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The Population and Civil Registration Office (DUKCAPIL) of Palangka Raya City uses WLAN network technology as an internet access service for its employees. The large number of users and not yet conducted research on the quality of WLAN network services causes problems to arise and network disruptions in the service. The purpose of this study is to obtain the parameter values of delay, packet loss, throughput and jitter which are measures of WLAN network performance quality. This research uses the research action method, while to retrieve data is done by download and upload methods. The results showed that in general the quality of service at the Population and Civil Registration Office of Palangka Raya City was medium to best with details as follows: for delay and jitter parameters included in the hight category, packet loss parameters included in the best category and throughput included in the medium category.